In Vitro Evaluation of Corn Silk Extract as a Potential Alternative Therapy for Vulvovaginal Candidiasis - Liberty P.; Putra I. B.; Jusuf N. K.; Sari M. I. (Acta Medica Bulgarica, 2023)
To determine the effectivity of corn silk extract in inhibiting the growth of C. albicans.